The usurpation of political space by economic powers: on the subject of the "Rollerball" film - Sendín García, Miguel Ángel Sendín (Universidad Nacional del Litoral, 2016)
This article examines the film Rollerball, questioning whether economic powers have occupied the political space in modern societies.